Activated Oxytocin Neurons in the PVN-DVC Pathway in Asthmatic Rats - Chen, Zhe; Long, Li; Xiao, Jian; Liu, Nina; Dong, Rong (Frontiers in Neuroanatomy, 2020)
Asthma is a heterogeneous disease, and the mechanism may be involved in central nervous system. Previously we reported the amygdala may regulate asthma attack via hypothalamic paraventricular nucleus (PVN). This study aimed to investigate the distribution of oxytocin (OT) ergic neurons in PVN and the pathway from PVN to dorsal vagal complex (DVC) in asthmatic rats. An asthmatic rat model was employed, and immunohistochemistry was conducted to observe the changes in Fos and OT expression under asthma. A triple-labelled method, combined with wheat germ agglutinin-horseradish peroxidase (WGA-HRP) retrograde tracing and double immunohistochemistry, was used to observe the HRP/OT/Fos positive neurons distribution in PVN. The results showed that the neurons in PVN and DVC were activated during asthma attack, which were mainly located in the lateral, dorsal and medial subnuclei of PVN, and OT expressions in PVN were increased. Using WGA-HRP retrograde tracing and double immunohistochemistry, seven types of positive neurons were observed in PVN. Asthma attack may lead central sensitisation and during asthma attack, neurons in PVN and DVC were activated. OT neurons in PVN were closely related to asthma attack. The projecting from PVN to DVC might be involved in asthma attack.